Case reviews in ophthalmology - Friedman, Neil J.; Kaiser, Peter K. (Philadelphia, PA : Elsevier, 2023)
"Using a highly effective case study format, Case Reviews in Ophthalmology, 3rd Edition, incorporates both medical knowledge and clinical judgement to help you achieve the best possible results on practical exams. This carefully compiled study resource provides more than 165 relevant cases covering every aspect of the field: optics/refraction, neuro-ophthalmology/orbit, pediatrics/strabismus, external disease/adnexa, anterior segment, and posterior segment. Large photos highlight each case, enhancing your knowledge and reinforcing key aspects of diagnosis"--
Preface - Acknowledgments - Abbreviations - 1. Optics/refraction - 2. Neuro-ophthalmology/orbit - 3. Pediatric ophthalmology/strabismus - 4. External disease/adnexa - 5. Anterior segment - 6. Posterior segment - Index of cases - Index.
Includes indexes.
"Enhanced digital version included"--cover.
Previous edition: published as by Neil J. Friedman, Peter K. Kaiser, 2018.
Keywords: Eye -- Diseases -- Case studies; Ophthalmology -- Case studies; Eye Diseases; Ophthalmology; Eye -- Diseases; Ophthalmology; Case Reports; Examination Questions; Case studies